A review of ontology development aspects - Law N.L.L.M.F.; Mahmoud M.A.; Tang A.Y.C.; Lim F.-C.; Kasim H.; Othman M.; Yong C. (Science and Information Organization, 2023)
Artificial intelligence; Interoperability; Semantic Web; Applications domains; Component; Development methodology; Development platform; Literature studies; Ontology applications; Ontology development; Ontology's; Semantic interoperability; Semantic-Web; Ontology